2002
DOI: 10.1542/peds.110.3.497
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Role of Depression in the Development and Persistence of Adolescent Obesity

Abstract: Depressed adolescents are at increased risk for the development and persistence of obesity during adolescence. Understanding the shared biological and social determinants linking depressed mood and obesity may inform the prevention and treatment of both disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
604
7
15

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 745 publications
(655 citation statements)
references
References 53 publications
29
604
7
15
Order By: Relevance
“…Depression, smoking and alcohol consumption Contrary to other studies (26,28) , we found no association between overweight and depression and smoking. In the bivariate analysis, daily alcohol consumption was significantly higher among men, in line with other studies reporting heavy alcohol intake to be positively related to overweight and obesity (29) .…”
Section: Physical Activitycontrasting
confidence: 99%
“…Depression, smoking and alcohol consumption Contrary to other studies (26,28) , we found no association between overweight and depression and smoking. In the bivariate analysis, daily alcohol consumption was significantly higher among men, in line with other studies reporting heavy alcohol intake to be positively related to overweight and obesity (29) .…”
Section: Physical Activitycontrasting
confidence: 99%
“…We used an internal definition, based on percentiles, to provide sufficient numbers for the analyses as has been performed in previous studies on adolescent obesity and also in this sample. 14,22 BMI at the age of 31 years was calculated using the measured data of body weight (kg, in underwear) and height (cm, without shoes) obtained during the clinical examination or the weight and height asked in the questionnaire if the measured data from the clinical examination were not Obesity and depression A Herva et al available. In 70% of the subjects weight and height were measured.…”
Section: Measurementsmentioning
confidence: 99%
“…13 On the other hand, recent studies have mostly observed an increased risk for depression among the obese. 14,15 Most of the epidemiological studies concerning the association between obesity and depression have been cross-sectional. 15,16 There is not much knowledge of whether obesity increases the risk of depression in later life.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Depressed mood, mainly in adolescents, also increases the risk for subsequent obesity even after controlling for baseline body weight. 8 Although obesity, by itself, does not appear to be systematically associated with psychopathological outcomes, subgroups of obese individuals have been identified who suffer substantially from psychiatric disorders, especially depression. [9][10][11] Thus, the depression risk may not be equally distributed among obese subjects and, in consequence, may contribute inconsistently to a subsequent CHD risk.…”
Section: Introductionmentioning
confidence: 99%